2013
DOI: 10.2459/jcm.0b013e328351674e
|View full text |Cite
|
Sign up to set email alerts
|

Association of cardiac changes with serum adiponectin and resistin levels in obese and overweight children

Abstract: In this study, even in asymptomatic obese and overweight children, cardiac structural and functional changes, such as increased left ventricular mass and diastolic dysfunction, were demonstrated. Although decreased adiponectin level was not related to cardiac changes, it was shown that decreased serum resistin levels in the obese cases lead to left ventricle hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…However, the mechanisms that account for the ability of resistin to predict human heart failure are unclear. In this regard, although associations between circulating resistin concentrations and left ventricular mass (LVM) have been demonstrated in a small study sample of children [17], no independent relations were noted in large adult population samples [18,19]. Further, in large samples only modest independent relations between circulating resistin concentrations and LV systolic function were reported [18,19].…”
Section: Introductionmentioning
confidence: 89%
“…However, the mechanisms that account for the ability of resistin to predict human heart failure are unclear. In this regard, although associations between circulating resistin concentrations and left ventricular mass (LVM) have been demonstrated in a small study sample of children [17], no independent relations were noted in large adult population samples [18,19]. Further, in large samples only modest independent relations between circulating resistin concentrations and LV systolic function were reported [18,19].…”
Section: Introductionmentioning
confidence: 89%
“…Current commercial assays offer the measurement of medium molecular weight adiponectin (MMW), and total adioponectin (Total). HMW has been shown to predict future weight gain [Hivert et al, ] and the ratio of HMW to Total has been found to be associated with obesity in children [Aknc et al, ]. However, it is unclear in some conditions such as coronary atherosclerosis whether HMW or the ratio of HMW/Total adiponectin provides the more accurate prediction of metabolic condition [Liang et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Low birth weight has previously been linked with high leptin and low adiponectin levels [ 59 ]. However, some studies have reported inconsistent findings regarding resistin in relation to low perinatal weight and obesity or overweight [ 59 , 60 , 61 , 62 ]. Therefore, the role of this adipokine in regulating insulin sensitivity and adipogenesis during the perinatal period is not yet fully understood [ 63 ].…”
Section: Discussionmentioning
confidence: 99%